Numerical modelling of LSF walls under combined compression and bending actions and fire conditions. (January 2023) - Peiris, Mithum; Mahendran, Mahen
Abstract: Numerical modelling of cold-formed steel walls used in determining the ambient temperature ultimate capacities has evolved from the use of idealised stud-only models to advanced models by employing sheathing and connection characteristics. Due to the convergence issues associated with elevated temperature structural models, attempts to incorporate sheathing are scarcely seen in the literature. In this study, the behaviour of light gauge steel framed (LSF) walls under combined axial and lateral loads and fire exposure was investigated by using stud-only and advanced structural finite element (FE) models. The advanced model is an improved single stud model which included gypsum plasterboard sheathing while also making models computationally less demanding. It incorporated material and geometric non-linearities, contact interactions, idealised in-plane restraints and explicit modelling of gypsum plasterboard sheathing, and was validated using full-scale fire test results. The predicted fire resistance levels (FRLs), failure modes, axial shortening and lateral deflection plots showed good agreement with fire test results. Furthermore, thermal FE models were also developed and validated against fire test results. They will be extended to obtain the time–temperature profiles of cavity insulated and non-insulated single and double plasterboard sheathed LSF walls exposed to fire for use in structural parametric studies. This paper summarises the findings of this study and proposes suitable recommendations for FE modelling of LSF walls under combined compression and bending actions and fire conditions. Highlights: Developed and validated stud-only and advanced FE models to predict the FRLs of LSF walls under combined loading. Structural FE models were validated by using FRLs, failure modes and load–displacement curves from fire tests. Thermal FE models were developed and validated using temperature–time curves of stud and sheathing surfaces. Stud-only model predicted the FRLs under pure compression reasonably well but not for combined loading. Highlighted the benefits of advanced FE model to predict the FRLs of LSF walls under combined axial and lateral loading.